Design and manufacturing of a new CNC gantry machine with double motion feed drive system / Seyed Reza Besharati - Seyed Reza, Besharati (2015)
The CNC machine tools are spatial machines that are able to control computer. There are two types of machine tools structure, C-frame and gantry-frame. A CNC gantry machine tool is defined as a computer numerically controlled machine that is programmed and controlled through a computer. Its CNC controller offers very short setup time flexibility to run batches of one to several thousand. Today, the CNC gantry machines are widely used in manufacturing combined with software programs to efficiently and consistently create different products for large companies or even single consumers. The CNC gantry machine is used in the manufacturing sector including drilling, milling, reaming, boring and counter boring. Parts can be grooved and threaded with CNC milling centers; they can be transformed into CNC lathes, CNC drill and tap areas; for CNC grinding; and used in conjunction with routers to make CNC wood engravers and letterers. The CNC gantry machine can be used to machine small, large, short and lengthy components. Currently, there are two types of such machines in the market. The first type has a moving worktable and fixed gantry and the second type has a moving gantry and fixed worktable. Each type has advantages and disadvantages. In this study, a new concept is proposed to improve the specifications and applicability of the first type of CNC gantry machine. In the new concept, reciprocal and simultaneous motion of the gantry and worktable is proposed as the gantry machine’s X-axis double motion mechanism. At the beginning of this study, the double motion mechanism is designed based on a rack and pinion system. A new anti-backlash system is proposed to compensate for transmission error and backlash (simultaneously) and for use in the double motion mechanism. The simulation results of the new anti-backlash system are discussed. Due to manufacturing limitations of the rack and pinion systems, a new double motion mechanism based on a ball screw system is proposed. Then, various designs of a new CNC gantry machine are presented. In this improvement process the problem is solved with the new design of a completed CNC gantry machine. The dynamic and static behavior of the final CNC gantry machine design is investigated via modal and static structural analysis using ANSYS software. The gantry’s natural frequency is designed to be 202 Hz in the first vibration mode, making the machine capable of working at higher speeds of up to 11530 rpm, which is suitable not only for rough cutting but also for finishing. The final design of the new CNC gantry machine is updated according to the obtained results. The increase in natural frequency during gantry design modification affects complexity, increasing the weight and manufacturing cost of the gantry. As such, five different gantry designs are selected for comparison. Four parameters, i.e., the first four natural frequencies, total deformation due to mechanical forces, weight and manufacturing cost are considered performance indices. One is selected among five designs mathematically and optimized by MOGA (multi-objective genetic algorithm) in ANSYS software. In the optimization process, the gantry’s natural frequency is maximized, thus minimizing the total gantry weight and deformation against mechanical forces. CNC gantry machine documents for manufacturing are prepared, followed by modeling, casting, machining and assembly. To evaluate and verify the design and analysis, an experimental modal test is performed. The experimental results show less than 11% error between the dynamic analysis and experimental test.